Особливості сучасної україномовної поезії в Польщі - Яручик, Віктор Павлович (Східноєвропейський національний університет імені Лесі Українки, 2013)
1. У статті йдеться про поетичний доробок україномовних письменників у Польщі. Автор намагається проаналізувати творчість митців Холмщини, Підляшшя та Лемківщини періоду кінця ХХ – початку ХХІ століття. Основна увага зосереджена на нових іменах у літературному процесі і проблематиці їхньої творчості. Автор робить спробу проаналізувати особливості віршування, якими користуються поети, котрі з різних причин живуть за межами материкової України. The article is about the poetic heritage of Ukrainian writers in Poland. The author tries to analyze the work of artists Holm, Podlasie and Lemko of the late XX  early XXI century. The main focus is on new names in the literary process and the problems of their work. The author makes an attempt to analyze the characteristics of poetry used by the authors, who for various reasons live outside of mainland Ukraine. It is important to compare the creative heritage of the older and younger generation of poets in Poland. On a thematic level authors tend to topics autopresentation and Ukraine is not always the lead. Interestingly, among the many artists are innovators and traditionalists, no matter which region they live. Most of the names of heroes article the reader probably will hear for the first time.
Keywords: поезія; творчість; літературний процес; письменник; автопрезентація